The impact of personality traits and abilities on entrepreneurial orientation in SMEs. (30th March 2022) - Leonelli, Simona; Masciarelli, Francesca; Fontana, Fabrizia
Abstract: Entrepreneurial orientation is especially important for economic growth, innovation, and employment. This paper investigates how entrepreneurs' narcissism and resilience affect the entrepreneurial orientation of small and medium sized enterprises. We identify two sides of entrepreneur narcissism: exhibitionism and manipulation. Using survey data from 114 firms, our results show that the exhibitionistic sides of narcissism and entrepreneur resilience have a positive effect on entrepreneurial orientation, while the manipulative side of narcissism has a negative impact. Our findings show also that resilience moderates the relationship between narcissism and entrepreneurial orientation. This study contributes to the understanding of the antecedents of entrepreneurial orientation.